FRI0454 Uveitis is associated to hypertension and cardiovascular disease in ankylosing spondylitis. (23rd January 2014) - Berg, I. J.; Semb, A. G.; van der Heijde, D.; Kvien, T. K.; Dagfinrud, H.; Provan, S. A.
Abstract : Background: Uveitis is a common feature of ankylosing spondylitis (AS) affecting approx. 30% of the patients. The literature describing the disease activity and co-morbidities in this subgroup is sparse. Objectives: To compare disease activity and co-morbidities in AS patients with and without uveitis. Methods: A cross-sectional study of AS patients recruited from a hospital cohort of AS patients diagnosed according to the mod New York criteria. Frequency of co-morbidities was assessed from questionnaires and interviews, clinical examination was performed, serum markers analyzed and composite measures were used to assess disease activity and function (ASDAS-CRP, BASDAI, BASFI and BASMI). Statistical analyses were performed in SPSS 20 using bivariate test as appropriate. Associations between uveitis and disease activity were analyzed using multiple linear regression models with adjustments for age, gender and use of TNF-inhibitors. Associations between uveitis and co-morbidities were analyzed using logistic regression models with adjustments for age and gender. These models were also adjusted for possible confounders: ASDAS, CRP (in separate models) and smoking habits. Results: 159 AS patient participated in the study, and as many as 84 (52.8%) had experienced one or more episodes of uveitis. The patients with uveitis were non-significantly older than patients without uveitis (uveitis vs. no uveitis): 52.1 vs. 48.8, p=0.08. There were no significant differences regarding other demographic data (gender, education>12 years, smoking habits) or in the acute phase reactants (ESR, CRP). More patients with uveitis used TNF-inhibitors (25.0 % vs. 10.8%, p=0.02), while there were no significant differences in use of NSAIDS or DMARDS. In adjusted analyses uveitis was associated to higher disease activity and worse function for all measurements, but only statistically significant for BASFI (figure 1 ). Uveitis was associated to hypertension and atherosclerotic cardiovascular disease (CVD), and the difference remained significant after adjustments for confounders (figure 2 ) Image/graph: Conclusions: We found numerically but non-significant associations between uveitis and disease activity, indicating that presence of uveitis represent a more active disease state. Further we found a significant association, after adjustment for CRP and smoking, between uveitis and atherosclerotic CVD and hypertension indicating that patients with uveitis are at a higher risk of CVD. Disclosure of Interest: None Declared